PROFESSIONAL LEARNING COMMUNITY MANAGEMENT TO CREATE HAPPY LEARNING DEVELOPMENT IN THE NEXT NORMAL ERA : A CASE STUDY OF THE KRUEWAIWITTAYAKOM SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE CHANTHABURI TRAT - Audnonglao, Watcharin; Nilkote, Reongwit; Warabamrungkul , Theerangkoon (Journal of MCU Nakhondhat, 2023)
The objectives of this research were: 1) to study the management of professional learning communities in the next normal era; 2) to synthesize factors that affect happy learning in the next normal era, and 3) to propose professional learning community management guidelines for the development of happy learning in the next normal era. It is qualitative research. Collect data with in-depth interviews, focus groups, and participatory observations. Tools include in-depth interviews, 10 key informants, and group discussions, 5 key informants. It is selective, content analysis, triangular investigation, and descriptive presentation. The results of the research showed that 1) the management of professional learning communities in the next normal era consisted of 1.1) having a shared vision to work with leadership, 1.2) aiming to develop the quality of learners, 1.3) learning for professional development in a friendly manner, 1.4) developing collaborative teaching and learning towards best practices, and 1.5) reflecting on work and exchanging performances. 2. Factors affecting happy learning in the next normal era consisted of 4 aspects: 2.1) teacher factor, 2.2) environment factor, 2.3) learner factor, and 2.4). organizing learning activity factor. And 3. Guidelines for the management of professional learning communities leading to happy learning development in the next normal era, it was found that there were 2 forms, namely 3.1) Formal form is a form of operation according to the procedures specified by the educational institution. And 3.2). Informal is a form of collaborative care for teachers in times of need.